Sistem Irigasi Otomatis Budidaya Anggrek Menggunakan Metode Fuzzy K-Nearest Neighbor (FK-NN) Berbasis Internet of Things - Maysandra, Adisty; Ikhsan, Muhammad (Jurnal Algoritma, 2025)
This study develops an automatic irrigation system for orchid plants based on the Internet of Things (IoT) using the Fuzzy K-Nearest Neighbor (FK-NN) method. This system utilizes soil moisture, temperature, and air humidity sensors to monitor environmental conditions and determine plant water needs. Sensor data is analyzed using FK-NN to determine the optimal irrigation pattern, automatically controlling the water pump through a drip irrigation system. Testing shows that the system accuracy reaches 95.23%, with good performance in classifying soil moisture conditions. This system is equipped with an Android application for remote monitoring and manual control. This study provides an efficient and accurate solution for orchid irrigation, supporting optimization of water use and increasing productivity.